CpG island methylation profile in non-invasive oral rinse samples is predictive of oral and pharyngeal carcinoma. Issue 1 (December 2015) - Langevin, Scott; Eliot, Melissa; Butler, Rondi; Cheong, Agnes; Zhang, Xiang; McClean, Michael; Koestler, Devin; Kelsey, Karl
Abstract Background There are currently no screening tests in routine use for oral and pharyngeal cancer beyond visual inspection and palpation, which are provided on an opportunistic basis, indicating a need for development of novel methods for early detection, particularly in high-risk populations. We sought to address this need through comprehensive interrogation of CpG island methylation in oral rinse samples. Methods We used the Infinium HumanMethylation450 BeadArray to interrogate DNA methylation in oral rinse samples collected from 154 patients with incident oral or pharyngeal carcinoma prior to treatment and 72 cancer-free control subjects. Subjects were randomly allocated to either atraining or atesting set. For each subject, average methylation was calculated for each CpG island represented on the array. We applied a semi-supervised recursively partitioned mixture model to the CpG island methylation data to identify a classifier for prediction of case status in thetraining set. We then applied the resultant classifier to thetesting set for validation and to assess the predictive accuracy. Results We identified a methylation classifier comprised of 22 CpG islands, which predicted oral and pharyngeal carcinoma with a high degree of accuracy (AUC = 0.92, 95 % CI 0.86, 0.98). Conclusions This novel methylation panel is a strong predictor of oral and pharyngeal carcinoma case status in oral rinse samples and may have utility in early detection and post-treatment follow-up.